The “9.9 Super Shopping Day” Advertisement Video and Its Impact on Shopee Users on TikTok - Nada Farah Amrudhia; Sylvie Nurfebiaraning (Kanal: Jurnal Ilmu Komunikasi, 2021)
The research objective of this study is to find out the influence and how much the influence of Shopee’s In-Feed Native Video Ad on TikTok App toward Audience Attitude. This study focuses on Shopee’s In-Feed Native Video advertising “9.9 Super Shopping Day” version on TikTok by involving one independent variable which is advertising (Variable X) measured using sub variables which are heard word, color, music, picture, seen word and movement. Dependent variable which is Audience Attitude (Variable Y) measured with cognitive,affective and conative aspect. The method used in this study is quantitative with data collection techniques through surveys to 400 respondents, which are followers of the @shopee_id account on the TikTok application. The results showed that the influence of the Advertising variable (X) on the Audience Attitude variable (Y) was 58,6%. While the remaining 41,4% is influenced by other factors not examined. The t test results show that the advertising variable (X) has a t value greater than the t table value because t count (23.742)> t table (1.96),then H0 is rejected and H1 is accepted. This means that Shopee’s In-Feed Native Video Ad “9.9 Super Shopping Day” version on TikTok App have an impact on audience attitude.